Bilateral Toric Phakic Intraocular Lens Implantation for Correction of High Myopic Astigmatism in a Patient with Marfan Syndrome with Lens Coloboma: A Case Report - Singh, Bhupesh (Case Rep Ophthalmol, 2021)
Marfan syndrome (MFS) is known to cause significant refractive error. Treatment options are limited in this condition for correcting refractive error. Clear lens exchange is done in these cases, but complication rates are high. Loss of accommodation is another concern in these young adults. We report toric phakic intraocular lens (pIOL) implantation in improving the uncorrected visual acuity (UCVA) in a known case of MFS with lens coloboma. A 22-year-old female patient with MFS with inferior lens coloboma underwent bilateral toric pIOL implantation in the same sitting. Pre- and post-operative UCVA and best-corrected visual acuity were assessed. Central and peripheral vaulting of the pIOL in relation to the natural lens was also assessed. UCVA improved from 20/500 to 20/20 in the right and 20/550–20/20 in the left eye. Marked central vaulting with partial peripheral vaulting was achieved. There were no post-operative complications. Phakic IOL implantation surgery could be an effective approach to achieve excellent uncorrected refractive outcome in patients with MFS to treat high myopia.